Effects of Covid-19 Pandemy Over Maritime Transport: An Evaluation of Supply-demand Balance - Danisman, Murat; Akkartal, Erkut (Archives of Business Research, 2021)
This research aims to examine the covid-19 pandemic measurements taken in maritime transport and their possible effects on the supply-demand equilibrium and consequently on the freight market. Covid-19 virus which infected quite large geographic area and people within very short time affects negatively not only every part of our life but also the production and service sector within the globalised world. This is mainly because the future tendency and further effects of this virus are unpredictable. Because of that, most countries are focused firstly on measurements to be taken to reduce the spreading speed of the virus. Although measurements and restrictions seem reduced spreading speed in some countries in short term, those measurements increase the operating costs of production and service companies. On the one hand reduction on cargo movements due to low demand and increasing operation cost due to measurements, have effected the supply-demand equilibrium of maritime transportation. This research examined the effects of already taken and could be revised measurements due to the present situation and possible future tendency of covid-19, and its consequential results on the freight market.